Retrospective and prospective studies of transmissible viral proventriculitis in broiler chickens in Brazil. (May 2021) - Leão, Philipe A.; Amaral, Camila I.; Santos, Willian H. M.; Moreira, Matheus V. L.; de Oliveira, Leticia B.; Costa, Erica A.; Resende, Mauricio; Wenceslau, Raphael; Ecco, Roselene
We investigated the occurrence and pathologic findings of transmissible viral proventriculitis (TVP) associated with the chicken proventricular necrosis virus (CPNV) in commercial broiler chickens in southeastern Brazil. Seventy-three broilers, 25–36 d old, with a history of reduced growth, were referred to our veterinary pathology services from 2013 to 2017. Broilers were clinically examined, weighed, and euthanized for postmortem examination. Broilers of different ages with proventricular histologic lesions were positive for CPNV by RT-PCR; however, the intensity of histologic lesions was higher among 33-d-old animals, and viral RNA detection was more frequent among those that were 28 d old. In the proventriculi of 35 of 73 (48%) broilers, lesions were characterized by glandular epithelial necrosis, lymphoplasmacytic and histiocytic infiltrates, and metaplasia of glandular epithelium to ductal epithelium. In 24 of 73 (36%) broilers with histologic TVP-compatible lesions, CPNV was detected by RT-PCR for the viral protein 1 ( VP1 ) gene. Broilers with histologic lesions were lighter than expected compared to the Cobb 500 standard weight. TVP has not been reported previously in broiler chickens in Brazil, to our knowledge.